Characterization of the Canine Retinal Vasculature With Optical Coherence Tomography Angiography: Comparisons With Histology and Fluorescein Angiography - Ripolles-Garcia, Ana; Ruthel, Gordon; Ying, Gui-Shuang; Chen, Yineng; Cuenca, Nicolas; Aguirre, Gustavo D.; Beltran, William A. (Frontiers in Neuroanatomy, 2021)
Purpose: To present a methodology for quantification of the canine retinal vasculature imaged by optical coherence tomography angiography (OCTA) and validate this approach by comparison with fluorescein angiography (FA) and confocal imaging of retinal wholemounts labelled by immunohistochemistry (IHC). Methods: Six normal adult dogs underwent retinal OCTA imaging in both eyes. The images extracted from the different microvascular plexuses at eight retinal locations spanning the central and mid-peripheral fundus were analyzed using the AngioTool software. FA was performed in one eye and was compared to the OCTA images. Six eyes from three dogs were processed by IHC to examine the retinal vasculature. Results: A total of four retinal plexuses were identified by OCTA in the canine retina, and their density and topographical pattern varied with eccentricity. OCTA offered improved resolution over FA with the advantage of allowing imaging of the individual plexuses. Detection by OCTA of small vessels within the deep capillary plexus was possible and approached the level of resolution achieved with ex vivo imaging of the retinal vasculature by confocal microscopy/IHC. The plexuses herein described are analogous to human retinal vasculature. Conclusion: OCTA can be used to image and quantify non-invasively the vascular retinal networks of the canine retina. We provide normative data in eight different retinal locations that can be imaged non-invasively with this technology. This could support analysis of retinal vascular changes associated with disease and following therapeutic intervention.